An architecture to facilitate the integration of human workers in Industry 4.0 environments - Sparrow, D. E.; Kruger, K.; Basson, A. H. (International journal of production research, 2022)
While Industry 4.0 research has predominantly focussed on the connection of machines and digital systems and solutions, it is important to consider the role of human workers within the envisaged Industry 4.0 environments. This paper presents the concept of a digital administration shell to support the integration of humans in Industry 4.0 environments and an architecture for the development of such an administration shell. The Biography-Attributes-Schedule-Execution (BASE) architecture builds on holonic systems principles and is guided by the requirements and responsibilities of the Resource Holon, as developed in the Holonic Manufacturing Systems paradigm. The functionality and value of the BASE architecture administration shell is demonstrated by means of a case study implementation.